Control of Meloidogyne javanica in banana by endophytic bacteria - de Souza Gleika Larisse Oliveira Dorásio; Ribeiro Regina Cássia Ferreira; Xavier Adelica Aparecida; Nietsche Silvia; de Castro Moreira Thaís; Martins Maria Josiane; Pimenta Samy; Mizobutsi Edson Hiydu; dos Santos Neto José Augusto; Santos Isabela Oliveira (Open Agriculture, 2024)
The aim of this work was to evaluate the effect of 40 endophytic bacteria isolates on the control of Meloidogyne javanica in ‘Prata-Anã’ banana seedlings. Two experiments were carried out in a completely randomized design with eight replicates. In each trial, 20 bacteria isolates and control were evaluated. Bacterial suspensions were applied to substrates during the acclimatization of seedlings at 15 and 30 days. On the 31st day, seedlings were transplanted into pots and soil was infested with M. javanica egg suspension at 8 days. After 90 days, the following variables were evaluated: number of galls, egg masses, eggs per root, reproduction factor (RF), second-stage juveniles, and shoot dry matter. The results of nematological variables were submitted to Principal Components Analysis. In trial I, the variables that most contributed to data variability were as follows: number of eggs and RF. In trial II, RF had greater influence. Of the 40 isolates evaluated, 39 reduced RF, and of the 20 isolates evaluated in the first trial, all reduced the number of eggs per root. Bacillus methylotrophicus EB26, Bacillus cereus EB25, and Bacillus sp. EB37 isolates stood out in the control of nematodes, with RF reduction above 80%.